THE DOCTRINE OF SOVEREIGN IMMUNITY ON WARSHIP WRECKS IN INDONESIAN WATERS ACCORDING TO UNCLOS 1982 - Fatchurrohman; Wagiman (Media Inovasi Pendidikan dan Publikasi, 2024)
Warship wrecks in Indonesia are twofold: those owned by foreign governments, and those owned by the Government of Indonesia, considered hero's graves in the middle of the sea. Sovereign immunity under the 1982 UNCLOS Convention is not explicit for active warships or their wrecks. (1) How does Indonesia provide sovereign immunity to warships?; (2) What about the question of foreign countries about their warship wrecks in Indonesian waters? The use of normative juridical legal research methods, with primary legal materials: 1982 UNCLOS Convention, secondary: legal doctrine on the status of warship wrecks, and tertiary legal materials. The results of the study explain (1) Indonesia only recognizes the sovereign immunity of warships on duty. (2) Indonesia does not grant the wishes of foreign countries over its war wrecks, for the main reason of national interest in the form of shipping safety. The latest regulation on the management of sunken ship cargo objects was issued because the old regulation was not in accordance with legal developments and needs. Researcher's suggestions: (1) Indonesia must regulate which warship wrecks can be explored and which cannot. (2) Indonesia must more strictly supervise the exploration of sunken ship cargo objects.